Manajemen Pendidikan Karakter dalam Pengembangan Kecerdasan Emosional Santri di Studi Pondok Pesantren Madrasatul Qur’an Sabak Permai Kota Siak Sri Indrapura Riau - M Aziz Nasrullah; Marita Lailia Rahman; Badrus Badrus (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This study aims to analyze the planning, implementation, and supervision of character education management in developing the emotional intelligence of students at Pondok Pesantren Madrasatul Qur’an Sabak Permai, Siak Sri Indrapura, Riau. The background of this research is the phenomenon of character degradation among students as a result of rapid technological advancement and social change. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation. The results show that the planning of character education is formulated based on the pesantren’s vision, mission, and goals, which emphasize the formation of students’ character. Implementation is carried out through structured and consistent daily activities to foster emotional intelligence, such as discipline, role modeling, habituation, and spiritual development. Supervision is conducted continuously through program evaluation by the pesantren administrators. The findings indicate that character education management plays a strategic role in shaping students who not only have strong character but also stable and adaptive emotional intelligence. The implication of this study highlights the need to strengthen character education management within the pesantren education system to face the challenges of modern development.